2013
DOI: 10.1186/1471-230x-13-72
|View full text |Cite
|
Sign up to set email alerts
|

Different healing process of esophageal large mucosal defects by endoscopic mucosal dissection between with and without steroid injection in an animal model

Abstract: BackgroundStricture formation is one of the major complications after endoscopic removal of large superficial squamous cell neoplasms of the esophagus, and local steroid injections have been adopted to prevent it. However, fundamental pathological alterations related to them have not been well analyzed so far. The aim of this study was to analyze the time course of the healing process of esophageal large mucosal defects resulting in stricture formation and its modification by local steroid injection, using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 37 publications
4
51
1
Order By: Relevance
“…have administered triamcinolone not in the muscularis propria, but in the remaining submucosal tissue after partial EMR in dogs: the study was not designed to assess the stricture rate, but the authors showed that steroid injection deepened the oesophageal ulcers and delayed epithelialisation . This last finding was also supported by another recent animal study …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have administered triamcinolone not in the muscularis propria, but in the remaining submucosal tissue after partial EMR in dogs: the study was not designed to assess the stricture rate, but the authors showed that steroid injection deepened the oesophageal ulcers and delayed epithelialisation . This last finding was also supported by another recent animal study …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows what remains of the oesophageal wall after EMR and the two main modes of wound healing. Most of our understanding of oesophageal healing and stricture formation derives from the application of general paradigms of scar tissue formation in the animal oesophagus, or in other human organs, such as the stomach or skin . The first step is an epithelial injury, leading to a loss of the barrier function of the epithelium, and the exposure of the submucosal space to several kinds of insults: mechanical through food boluses, chemical through acid or bile reflux and microbial due to the oesophageal bacterial and fungal flora.…”
Section: Introductionmentioning
confidence: 99%
“…In the next 2 weeks, inflammation decreases and angiogenesis increases. By around 28 days after the procedure, in addition to dense fibrosis in the SM, the muscle layer also shows significant atrophy and fibrosis, which further reduces contractibility and flexibility of the esophageal wall …”
Section: The Submucosamentioning
confidence: 99%
“…Therefore, effective, simple, and safe preventions are urgently needed. The pathophysiology of stricture may involve inflammation, collagen synthesis, and the formation of fibrous in the process of postoperative mucosal healing and the scarring of the tissues …”
Section: Discussionmentioning
confidence: 99%